1,2,4-Triazole-conjugated Fluoroquinolones as Potential Candidates for New Antibacterial Agents - Uygun Cebeci, Yıldız; Karaoglu, Sengul A. (Letters in Organic Chemistry, 2024)
In this study, synthesis of 1,2,4 triazole-fluoroquinolone hybrid compounds was realized. 7a-d hybrid compound was obtained as a result of mannich reaction with 6a-b triazole compounds norfloxacin and ciprofloxacin. 1H-NMR, 13C-NMR, Mass Spectrometry and Elemental Analysis confirmed the structures of all synthesized compounds. The antimicrobial activities of all compounds were investigated, and it was observed that 7a-d compounds, which are mannich bases, showed excellent activity.
Keywords: antibacterial